Intellectual Property Rights and Entry into a Foreign Market: FDI vs. Joint Ventures - Alireza Naghavi; Dermot Leahy (Fondazione Eni Enrico Mattei (FEEM), 2006)
We study the effect of the intellectual property rights (IPR) regime of a host country (South) on a multinational's decision between serving a market via greenfield foreign direct investment to avoid the exposure of its technology or entering a joint venture (JV) with a local firm, which allows R&D spillovers under imperfect IPRs. JV is the equilibrium market structure when R&D intensity is moderate and IPRs strong. The South can gain from increased IPR protection by encouraging a JV, whereas policies to limit foreign ownership in a JV gain importance in technology intensive industries as complementary policies to strong IPRs.
Keywords: O34; F23; O32; F13; L24; O24; 330; Joint Ventures; Intellectual Property Rights; Technology Transfer; R&D Spillovers; FDI Policy; Globalisierung; Multinationales Unternehmen; Immaterialgüterrechte; Direktinvestition; Joint Venture; Oligopol; TRIPS; Ökonometrisches Modell